2006
DOI: 10.1007/s00204-006-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic cytosolic glutathione S-transferase activity and expression of its class-P during prenatal and postnatal period in rats treated with aflatoxin B1

Abstract: The effect of aflatoxin B1 (AFB1) on the expression of glutathione S-transferase-P (GST-P) which is the major isoform of GST in developmental stages has been investigated in rat liver during prenatal and postnatal stages. Following administration of AFB1 (0, 0.5, 1.0, 2.0, 3.0 or 4.0 mg/kg bw) injected I.P on day 8.5 of gestation the number of dead or reabsorbed fetuses and malformed embryos were recorded. Then the fetal livers were processed for measurement of total GST and GST-P activities, using 1-chloro-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…The reason of elevation in hepatic enzyme activities (ALT and AST) in chickens receiving aflatoxin could be the hepatic damage and leakage of enzymes in the bloodstream. Similar data have been reported previously (Fatemi et al, 2006;Hashem & Mohamed, 2009;Quezada et al, 2002). Although in the present study, a diet containing 3 ppm aflatoxin significantly increased serum AST and ALT but this finding is in contrast to the finding of Huff et al (1992) that has reported aflatoxin caused a decrease in the activity of AST.…”
Section: Discussioncontrasting
confidence: 57%
“…The reason of elevation in hepatic enzyme activities (ALT and AST) in chickens receiving aflatoxin could be the hepatic damage and leakage of enzymes in the bloodstream. Similar data have been reported previously (Fatemi et al, 2006;Hashem & Mohamed, 2009;Quezada et al, 2002). Although in the present study, a diet containing 3 ppm aflatoxin significantly increased serum AST and ALT but this finding is in contrast to the finding of Huff et al (1992) that has reported aflatoxin caused a decrease in the activity of AST.…”
Section: Discussioncontrasting
confidence: 57%
“…These links represent the primary biochemical lesion produced by aflatoxins and determine the reduction in protein biosynthesis and, consequently, in the animal growth. Conversely, aflatoxin-epoxide can also be connected with glutathione, constituting an important way of detoxification of this composite (Fatemi et al, 2006). However, the level of glutathione in the cells is dependent on the availability of cysteine, an amino acid partially formed by methionine.…”
Section: Nutritional Interactionsmentioning
confidence: 99%
“…Increase in CYP450 activity in DMH-treated rats confirming its role in detoxification of DMH as a carcinogen [6][7][8][9]. Also, induction of GST activity, one of the main biotransformation enzymes in phase II detoxification pathway, in liver of DMH treated rats may be due to its effective role in detoxification of carcinogenic metabolite of DMH [10,45]. In this connection, caraway seeds as well as oils decrease the hepatic CYP450 elevated in DMH treated rats.…”
Section: Discussionmentioning
confidence: 99%